Global, European and National Challenges in the Enlarged European Union with Emphasis on the New Member Countries - Inotai, ANDRÁS (Papeles del Este, 2006)
The enlarged and further enlarging EU faces challenges on three levels: global, European and national. The article looks at these challenges in general, and from the point of view of the new member countries, in particular. It identifies some of the basic policy dilemmas of the new members with substantial impact on the future of the European integration as a whole. They include the policy mix in order to sustain the already started catching-up process to more developed EU members, the mixture of competitiveness and social welfare, answers to an increasingly two-way process of industrial relocation and the right timing of membership in the EMU. The last part of the paper deals with key future requirements of a successful EU, such as vision, leadership and new social mentality.In this context, the necessity of an increasing role of the new members in shaping the future of Europe is argued for.